Discussions on child development a consideration of the biological, psychological, and cultural approaches to the understanding of human development and behaviour - World Health Organization. Study Group on the Psychobiological Development of the Child (New York International Universities Press, 1953)
Annual
Keywords: Child development -- Congresses